Seal-skinners sealing in chono, aónikenk and chilote territory, 1830-1845 - Mayorga Zúñiga, Marcelo (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
Towards the end of the XVIII century and the beginning of the XIX century, in the context of a period of expansion on the part of European nations and the nascent North American republic, the commercial hunting of fur seals began to develop, and in this sense, the southern end of America became one of the main areas of their incursions. This work seeks to contribute to know more background regarding the presence of this group of navigators, in relation to the sustained interaction with the austral aborigines, as well as, regarding hunting activities. The study is based on unpublished documents, specifically American sealing ship logs. It is hypothesized that this commercial activity was much more than a transitory wandering dedicated to obtaining and collecting skins for distant markets, on the contrary, fur-seal hunters established a close relationship with the aborigines who populated these territories, in addition to generating a gradual process of familiarization with geography.